Nanocarriers for intracellular co-delivery of proteins and small-molecule drugs for cancer therapy - Cheng, Zhihong; Li, Yongshuang; Zhao, Duoyi; Zhao, Wei; Wu, Meng; Zhang, Weilin; Cui, Yan; Zhang, Peng; Zhang, Zhiyu (Frontiers in Bioengineering and Biotechnology, 2022)
In the past few decades, the combination of proteins and small-molecule drugs has made tremendous progress in cancer treatment, but it is still not satisfactory. Because there are great differences in molecular weight, water solubility, stability, pharmacokinetics, biodistribution, and the ways of release and action between macromolecular proteins and small-molecule drugs. To improve the efficacy and safety of tumor treatment, people are committed to developing protein and drug co-delivery systems. Currently, intracellular co-delivery systems have been developed that integrate proteins and small-molecule drugs into one nanocarrier via various loading strategies. These systems significantly improve the blood stability, half-life, and biodistribution of proteins and small-molecule drugs, thus increasing their concentration in tumors. Furthermore, proteins and small-molecule drugs within these systems can be specifically targeted to tumor cells, and are released to perform functions after entering tumor cells simultaneously, resulting in improved effectiveness and safety of tumor treatment. This review summarizes the latest progress in protein and small-molecule drug intracellular co-delivery systems, with emphasis on the composition of nanocarriers, as well as on the loading methods of proteins and small-molecule drugs that play a role in cells into the systems, which have not been summarized by others so far.